The Last Straw : Diary of a Wimpy Kid Series #3 - Kinney, Jeff (New York : Amulet Books, 2009)
Middle-schooler Greg Heffley nimbly sidesteps his father's attempts to change Greg's wimpy ways until his father threatens to send him to military school.
Keywords: Middle schools -- Fiction; Schools -- Fiction; Family life -- Fiction; Diaries -- Fiction; Humorous fiction